Cathodes for Electrochemical Carbon Dioxide Reduction to Multi-Carbon Products: Part I : A focused review of recent highlights. Issue 1 (31st January 2023) - Macpherson, Harry; Hodges, Toby; Chuma, Moyahabo Hellen; Sherwin, Connor; Podbevšek, Urša; Rigg, Katie; Celorrio, Veronica; Russell, Andrea; Corbos, Elena C.
This is a focused review of recent highlights in the literature in cathode development for low temperature electrochemical carbon dioxide and carbon monoxide reduction to multi-carbon (C2+) products. The major goals for the field are to increase Faradaic efficiency (FE) for specific C2+ products, lower cell voltage for industrially relevant current densities and increase cell lifetime. A key to achieving these goals is the rational design of cathodes through increased understanding of structure-selectivity and structure-activity relationships for catalysts and the influence of catalyst binders and gas diffusion layers (GDLs) on the catalyst microenvironment and subsequent performance.